Study of Smart Cities Based on Human Capital (Case of Russian Research-Driven Towns as Proto-Smart Cities) - S. G. Kamolova; K. S. Kim; N. D. Aleksandrov (Управленческие науки)
Existent philosophical literature has been largely focusing on the ethical aspects and controversies of developing and using smart technologies such as AI and big data, whereas human capital and infrastructural environment as pre-existing factors have been covered by AI Ethics in a lesser extent. Most of the current research focuses on technical infrastructural aspects in the implementation of complex «smart projects», while insufficient attention is paid to the role of social capital. In order to widen the focus and to include human capital and infrastructural developments coming along with the increasing role of AI, the paper takes a novel look at philosophical underpinnings of smart cities and discusses the concept of the Russian Naukograd (literally from Russian – City of Science, or Researchers’ city, meaning a city which is developing as a community of scientists and academics) as a historical approach for smart city concept implementation. The authors apply theoretical methods of cognition (analysis, synthesis) as well as the case study approach to the Russian (Soviet) experience in forming research-driven cities in order to highlight the value of high scientific, industrial and educational capital («smart nation») as a fundamental factor for the stable long-term development of modern cities. The findings suggest that some concepts of the Russian Naukograd for example the focus on research and education are valuable and that investment in social capital (i. e., people) should stand on the same footing as investment in technology developing a smart city. In this approach the prefix «smart» may stand for «smart citizens/nations» as a pivotal framework at the initial stages of smart cities development.